COMPOSITION OF REFUSE DERIVED FUELS IN LATVIA AND ESTONIA IN COMPARISION WITH WORLDWIDE AVERAGE VALUES (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
Information about composition of RDF worldwide was collected using literature analysis. RDF samples produced in Latvia and Estonia were collected, those fractional and elemental composition analyzed using standard methods. Comparing obtained results with worldwide data we have found that the quality of local RDFs in general is higher than typical values, while elevated content of chlorine must be mentioned as a problem. Results also show that majority of chlorine in studied samples exists in organic form. Recommendations to overcome this problem have been developed.